PENERAPAN PEMBELAJARAN PENDIDIKAN AQIDAH AKHLAQ DALAM PENDEKATAN SOSIOLOGI UNTUK MEMBENTUK KARAKTER ISLAMI SISWA KELAS VI MI-PERSMIN WONOKROMO SURABAYA - Muis, Muhammad; Salik, Mohamad (STIT AL MULTAZAM, 2022)
The type of research used is qualitative research. The research approach uses interdisciplinarity, including: Sociological. Qualitative research stages using observation activity objects. Researchers found problems in Madrasah Ibtidaiyah Persmin Wonokromo in learning Aqidah Akhlaq which is still lacking in implementing it into everyday life, especially children in class VI. Based on these problems, it is necessary to have a solution so that moral education can really be carried out by class VI students. One way is for the teacher not only to teach in class but to provide good examples such as good role models, through exemplary methods students are able to have good morals in accordance with the teachings of the Islamic religion. using certain learning methods so that students can receive lessons well so that students can understand the material well so that good character is embedded in students. then we can see that to shape the character of students, a teacher must be a good example, not just teaching in class, but the teacher conducts learning with various exemplary methods such as speech and behavior, so that students can apply it to teachers and colleagues.